Type of Fatty Acids, Lipoprotein Secretion from Liver and Fatty Liver Syndrome in Laying Hens - Aydin, Rahim (International Journal of Poultry Science, 2005)
Unlike other vertebrates, liver is the main site of lipid biosynthesis and is particularly very active in egg laying adult females. Yolk lipids and proteins are secreted as lipoproteins under the influence of estrogen in the liver. When hepatic lipogenesis exceeds the capacity of fat transport as lipoproteins, triacylglycerols commence to accumulate in the liver, leading to fatty liver syndrome. Fatty liver syndrome is an important metabolic disorder in laying flocks after they reach peak in egg production. The liver is generally enlarged, pale and shows extreme infiltration of fat and hemorrhages. It is a problem associated with the transport of triacylglycerols from liver to the developing oocyte. The effect of type and level of certain fatty acids may play an important role in the occurrence of the disorder. There is a correlation between delta-9 desaturase enzyme activity and secretion of very low-density lipoproteins from the liver. Certain fatty acids (i.e. sterculic acid, conjugated linoleic acids) inhibit the activity of this enzyme in the liver and cause lower levels of oleic acid which has a significant role in the secretion of triacylglycerols from chicken hepatocytes compared to other fatty acids such as linoleic or palmitic acids.